Culture, geographies or accounting regimes: which are drivers for risk-taking in European and Asian banks? - Lopes, A. I. (Entrepreneurship, Business and Economics: Proceedings of the 15th Eurasia Business and Economics Society Conference, 2016)
Our goal is achieved using the Hofstede’s model of cultural dimensions that has become internationally recognized. A sample covering 41 countries from Europe and Asia and about 3150 bank-years observations was selected to represent low and high averse to risk characteristics. The research is conducted to investigate the influence of culture attributes of risk-taking on the reporting of some variables related to risk, identifying whether or not geographies or accounting regimes are also determinants. We use two proxies for risk-taking, namely, Provisions for Loan Losses and Risk-Weighted Assets. Our research is designed using a twofold perspective. First, we examine if the distribution of our proxies for risk taking are different between independent groups. We compare the outcomes based on groups clustered by national culture dimensions, geographies and accounting regimes. Secondly, we examine if culture is a determinant of banks that present higher or lower amounts of incurred and unexpected losses. Our findings suggest that national culture is (is not) a determinant for the probability of reporting higher or lower level of loans loss provisions (risk weighed assets). These findings are consistent for banks in different geographies (Europe vs. Asia) and subject to different accounting regimes (IFRS vs. local standards).